Hemophilia A in children: prophylaxis, physical activity and rehabilitation in the prevention of hemophilic arthropathy - Lubkowski, Michał; Zuzanna Leciej; Krzysztof Antczak (Journal of Education, Health and Sport, 2026)
Background: Hemophilia A is a rare X-linked genetic disorder characterized by a deficiency of coagulation factor VIII. A key clinical problem in children is recurrent joint bleeding (hemarthrosis), which leads to the development of chronic synovitis and progressive hemophilic arthropathy, the main cause of disability in this patient population. Aim: The aim of this study is to present the significance of modern bleeding prophylaxis, systematic physical activity, and physiotherapy in preventing musculoskeletal complications in children with hemophilia. Material and methods: An analysis of current literature and guidelines regarding replacement therapy (factor VIII concentrates) and non-factor therapy (emicizumab) was performed. The use of functional diagnostic tools was discussed, including the Hemophilia Joint Health Score (HJHS 2.1), functional performance tests (6MWT, TUG), goniometry, and modern methods of objective assessment of muscle strength and posture. Results: The introduction of early bleeding prophylaxis allows for a significant reduction in the number of joint bleeds. Physical activity, especially low-impact types (swimming, cycling), enhances dynamic joint stabilization by strengthening the muscular corset and improving proprioception. Contemporary physiotherapy, based on progressive resistance training and biofeedback, is safe and essential for maintaining musculoskeletal function, while objective diagnostics enable early detection of subclinical joint changes. Conclusions: Effective prevention of hemophilic arthropathy in children requires an integrated interdisciplinary approach. The combination of modern pharmacological treatment with regular physical activity and functional rehabilitation allows pediatric patients to achieve functional capacity comparable to their peers and minimizes the risk of permanent disability.